Characterization of an alkalophilic Bacillus brevis isolate with respect to its endo-(1,3-1,4)-β-glucanase gene, protein hyperproduction and the degS-degU operon - Louw, Maureen Elizabeth (Department of Molecular and Cell Biology, 2016)
Bibliography: pages 127-144.